Nastajanje evropske manjšinske zaščite - Stergar, Janez (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2001)
The paper "Minority protection in the light of European documents" from the international conference Europe and national minorities on the threshold of the third millennium (Gorica/Gorizia, Italy, November 26-27, 1993) has for years been ready to be published in the conference collection of papers, which, however, was never published. Although codification of national minority protection in Europe has since then made considerable progress, a number of questions remains unanswered, especially as regards the promotion of international norms of protection. The author's survey is also a testimony on Slovene views and endeavours in the dealt-with expert and political field in the years 1992 and 1993. Considering the conference programme, the article does not deal with the activities of the Conference (Organization) for Security and Cooperation in Europe, nor with cooperation in the field of minorities. Apart from some subsequent notes, the text has later not been updated and complemented, as a number of more recent surveys is available.
Keywords: narodne manjšine; človekove pravice; human rights; pravice manjšin; pravna ureditev; pravno varstvo